2022
DOI: 10.1038/s41598-022-15216-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yoga on cardiometabolic risks and fetomaternal outcomes are associated with serum nitric oxide in gestational hypertension: a randomized control trial

Abstract: Gestational hypertension (GH) is associated with adverse cardiometabolic and pregnancy outcomes. Though yoga is known to be beneficial in pregnancy, the effects of yoga rendered for twenty weeks starting from 16th week of gestation in pregnant women having risk of GH on the incidence of hypertension, cardiometabolic risks and fetomaternal outcomes have not been studied. A randomized control trial was conducted on 234 pregnant women having risk of GH receiving standard antenatal care (Control group, n = 113), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…There were a total of 61 studies that were incorporated in this analysis [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ,…”
Section: Resultsmentioning
confidence: 99%
“…There were a total of 61 studies that were incorporated in this analysis [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ,…”
Section: Resultsmentioning
confidence: 99%
“…Yoga is a bene cial intervention for both pregnant women and their babies. Yoga intervention groups consistently had a decreased incidence of pregnancy-induced hypertension [11,24], and preeclampsia labour [10,11,22], lower levels of discomfort (p = 0.001) lower levels of stress (p < 0.001) Labor anxiety and depression, scores on relationship quality and a decreased frequency of babies born at a young gestational age. Lumbopelvic discomfort, stress, anxiety, and depression as well as high-risk pregnancy can be reduced by using yoga therapy [9,14,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies on high-risk pregnant women have been done [10][11][12], and one study on pregnant women who suffered pelvic pain [14]. During pregnancy, two studies on hypertension [23,24], were conducted. The rest of the studies focused on normal pregnant women.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A failure in this poorly understood mechanism could cause elevated BP in hypertensive pregnant women. Kuzhanthaivelu et al (Karthiga et al, 2021) reported a significant correlation between decreased NO levels and cardiovagal modulation using spectral analysis of heart rate variability. Therefore, hypertensive pregnancy disorders seem to reflect disruptions in the interaction of systems related to BP control that can be studied from a dynamic approach.…”
Section: Introductionmentioning
confidence: 99%